Dilution effects on ultrafine particle emissions from Euro 5 and Euro 6 diesel and gasoline vehicles. (November 2017) - Louis, Cédric; Liu, Yao; Martinet, Simon; D'Anna, Barbara; Valiente, Alvaro Martinez; Boreave, Antoinette; R'Mili, Badr; Tassel, Patrick; Perret, Pascal; André, Michel
Abstract: Dilution and temperature used during sampling of vehicle exhaust can modify particle number concentration and size distribution. Two experiments were performed on a chassis dynamometer to assess exhaust dilution and temperature on particle number and particle size distribution for Euro 5 and Euro 6 vehicles. In the first experiment, the effects of dilution (ratio from 8 to 4 000) and temperature (ranging from 50 °C to 150 °C) on particle quantification were investigated directly from tailpipe for a diesel and a gasoline Euro 5 vehicles. In the second experiment, particle emissions from Euro 6 diesel and gasoline vehicles directly sampled from the tailpipe were compared to the constant volume sampling (CVS) measurements under similar sampling conditions. Low primary dilutions (3–5) induced an increase in particle number concentration by a factor of 2 compared to high primary dilutions (12–20). Low dilution temperatures (50 °C) induced 1.4–3 times higher particle number concentration than high dilution temperatures (150 °C). For the Euro 6 gasoline vehicle with direct injection, constant volume sampling (CVS) particle number concentrations were higher than after the tailpipe by a factor of 6, 80 and 22 for Artemis urban, road and motorway, respectively. For the same vehicle, particle size distribution measured after the tailpipe was centred on 10 nm, and particles were smaller than the ones measured after CVS that was centred between 50 nm and 70 nm. The high particle concentration (≈10 6 #/cm 3 ) and the growth of diameter, measured in the CVS, highlighted aerosol transformations, such as nucleation, condensation and coagulation occurring in the sampling system and this might have biased the particle measurements. Highlights: Dilution and temperature effects on particle number emission. Comparison between tailpipe and CVS for particle number emission. Over-emission of particles from the CVS because of nucleation, condensation and coagulation. Tailpipe measurement as a complementary method to the CVS for exhaust particle sampling.